Cover Picture: Covalency‐Driven Preservation of Local Charge Densities in a Metal‐to‐Ligand Charge‐Transfer Excited Iron Photosensitizer (Angew. Chem. Int. Ed. 31/2019). Issue 31 (17th July 2019) - Jay, Raphael M.; Eckert, Sebastian; Vaz da Cruz, Vinícius; Fondell, Mattis; Mitzner, Rolf; Föhlisch, Alexander
Abstract : Charge‐density rearrangements after metal‐to‐ligand charge‐transfer excitation in an iron photosensitizer are investigated by R. M. Jay, A. Föhlisch et al. in their Communication on page 10742 ff. Using time‐resolved X‐ray absorption spectroscopy, surprising covalency effects are revealed that inhibit charge separation at the intramolecular level. Furthermore, the underlying mechanism is proposed to be in effect for all commonly used photosensitizers in light‐harvesting applications, which challenges the common perception of electronic charge transfer.